Yeast chromium and digestible lysine levels in finishing pigs subjected to high ambient temperatures - Alexandre Pereira dos Santos; Charles Kiefer; Karina Márcia Ribeiro de Souza Nascimento; Anderson Corassa; Jéssica Lira da Silva; Taynah Vieira Aguiar Farias; Stephan Alexandre da Silva Alencar; Denise de Santana Lima (Ciência Rural, 2021)
ABSTRACT: This study evaluated the effects of chromium yeast and digestible lysine levels on the performance and carcass characteristics of finishing pigs. Sixty-four barrows with an initial weight of 72.77 ± 7.20 kg and final weight of 119.44 ± 9.47 kg were used, distributed in a 2 x 2 factorial scheme, with two levels of chromium yeast (Cr0: 0 ppb and Cr800: 800 ppb) and two levels of digestible lysine (L0: recommended level and L+10%: 10%). The recorded air temperature of 30.9 ± 3.7 ºC during the experimental period was considered as heat stress. Performance variables were not influenced (P>0.05); however, L+10% showed an increase (P<0.05) in daily digestible lysine intake. Carcass characteristics of the animals were not influenced (P>0.05) by the chromium or digestible lysine levels. Supplementation with 800 ppb of yeast chromium and a 10% increase in the level of digestible lysine, isolated or associated, did not improve the performance and carcass characteristics of finishing pigs, subjected to high ambient temperatures.